Prognostic impact of moderate to severe anemia associated with renal dysfunction in patients with heart failure - Eri Noda; Shouji Matsushima; Toru Hashimoto; Yoshitomo Tsutsui; Kayo Misumi; Nobuyuki Enzan; Keimei Yoshida; Keisuke Shinohara; Takeo Fujino; Shunsuke Katsuki; Takafumi Sakamoto; Kazuya Hosokawa; et al. (Scientific Reports)
Abstract Moderate/severe anemia [hemoglobin (Hb) < 10 g/dL] is recommended to be treated in patients with renal anemia. However, the optimal therapeutic target for Hb levels in patients with heart failure (HF) is unknown. This study aimed to investigate the impact of severity of anemia, especially moderate/severe anemia, associated with renal dysfunction (RD: eGFR < 60 mL/min/1.73 m2) in HF patients. We analyzed 1,608 HF patients from the Japanese Cardiac Registry of Heart Failure in Cardiology (JCARE-CARD) database. Patients were classified based on the severity of admission anemia in the presence/absence of RD. Patients with RD and anemia were older, more likely to be female, and had a history of HF admission. The composite outcome was higher in RD and moderate/severe anemia (adjusted hazard ratio:2.120, 95% CI:1.559–2.881, p < 0.001) compared to RD and non/mild anemia (Hb ≥ 10 g/dL), non-RD and moderate/severe anemia, and non-RD and non/mild anemia (reference). During hospitalization, 6% and 10% of patients had improving and worsening RD and/or moderate/severe anemia, respectively. These status changes were associated with the post-discharge outcomes in HF patients. Moderate/severe anemia has a prognostic impact in HF patients with RD and may be an appropriate therapeutic target in HF.